The impact of perceived social support on psychological capital of firefighters: the chain mediating role of exercise self-efficacy and psychological resilience - Zhao, Bochuan; Tu, Haining; Zhang, Xinan; Yan, Yongtao; Su, Yuqi (Frontiers in Public Health, 2025)
BackgroundThis study explored how perceived social support affects firefighters' psychological capital through the chain mediating role of exercise self-efficacy and psychological resilience.MethodsFirefighters from a Jiangsu Province fire rescue team (N = 524, 95.3% response rate) completed the Perceived Social Support Scale (PSSS), Self-Efficacy for Exercise Scale (SEE), Connor-Davidson Resilience Scale (CD-RISC), and Psychological Capital Questionnaire (PCQ). Hierarchical regression analysis and Bootstrap method (5,000 resamples) tested the chain mediation model.ResultsThe sample consisted of 99.6% males, with ages mainly concentrated between 30-45 years, and an average service length of more than 10 years. Perceived social support was significantly positively correlated with psychological capital (r = 0.592), exercise self-efficacy (r = 0.527), and psychological resilience (r = 0.582); exercise self-efficacy correlated with psychological resilience (r = 0.579; all p < 0.001). The chain indirect effect (perceived social support → exercise self-efficacy → psychological resilience → psychological capital) was significant [95% CI (0.09, 0.18)].ConclusionPerceived social support enhances firefighters' psychological capital both directly and indirectly through sequential improvements in exercise self-efficacy and psychological resilience. Fire departments should create supportive team environments and integrate physical training with psychological resilience cultivation to improve firefighters' psychological capital and mental health.